A Diabetic Emergency One Million Feet Long: Disparities and Burdens of Illness among Diabetic Foot Ulcer Cases within Emergency Departments in the United States, 2006–2010 - Skrepnek, Grant H.; Mills, Joseph L.; Armstrong, David G. (PloS one, 2015)
To evaluate the magnitude and impact of diabetic foot ulcers (DFUs) in emergency department (ED) settings from 2006-2010 in the United States (US). This cross-sectional study utilized Agency for Healthcare Research and Quality (AHRQ) Healthcare Cost and Utilization Project (HCUP) National Emergency Department Sample (NEDS) discharge records of ED cases among persons ≥18 years with any-listed diagnosis of DFUs. Multivariable analyses were conducted for clinical outcomes of patient disposition from the ED and economic outcomes of charges and lengths of stay based upon patient demographic and socioeconomic factors, hospital characteristics, and comorbid disease states. Overall, 1,019,861 cases of diabetic foot complications presented to EDs in the US from 2006-2010, comprising 1.9% of the 54.2 million total diabetes cases. The mean patient age was 62.5 years and 59.4% were men. The national bill was $1.9 billion per year in the ED and $8.78 billion per year (US$ 2014) including inpatient charges among the 81.2% of cases that were admitted. Clinical outcomes included mortality in 2.0%, sepsis in 9.6% of cases and amputation in 10.5% (major-minor amputation ratio of 0.46). Multivariable analyses found that those residing in non-urban locations were associated with +51.3%, +14.9%, and +41.4% higher odds of major amputation, minor amputation, and inpatient death, respectively (p<0.05). Medicaid beneficiaries incurred +21.1% and +25.1% higher odds for major or minor amputations, respectively, than Medicare patients (p<0.05). Persons within the lowest income quartile regions were associated with a +38.5% higher odds of major amputation (p<0.05) versus the highest income regions. Diabetic foot complications exact a substantial clinical and economic toll in acute care settings, particularly among the rural and working poor. Clear opportunities exist to reduce costs and improve outcomes for this systematically-neglected condition by establishing effective practice paradigms for screening, prevention, and coordinated care.